Statistical Analysis of Short-Term Shoreline Change Behavior Along The Southern Cilacap Coasts of Indonesia - Mutaqin, Bachtiar W.; Munandar, Ariko V.; Jatmiko, Jatmiko; Harini, Rika; Purnama, Ig.L. Setyawan (Department of Urban and Regional Planning, Diponegoro University, 2024)
There is a threat of extreme waves and a moderate risk level of coastal erosion in Bunton Village. Based on the preliminary assessment, there is huge erosion of the shoreline and visible changes in the shoreline temporally. However, there is no statistical data on short-term shoreline change behavior in this area. Hence, this research aims to analyze statistically the short-term shoreline change behavior to understand the conditions and phenomena that occur on the coast of Bunton Village. Landsat images spanning the years 2002 to 2022, with recording intervals of 5 years each, were used to identify the shoreline data, which was later analyzed using the Digital Shoreline Analysis System (DSAS). Statistical analyses of short-term shoreline change behavior were obtained using the End Point Rate (EPR) and Net Shoreline Movement (NSM) approaches. Over a 20-year period, the Bunton coastal area experiences dynamic changes that are primarily due to erosion, with an average distance change of -255.5 meters and an average speed of -14.6 meters per year (very high erosion). The existence of the electric steam power plant (ESPP) in Adipala, which built a breakwater in 2012, has been proven to increase the erosion process. Shoreline change in this area can affect various landuses and tourism activities as well as trigger environmental problems in the Bunton coastal area.